MANAGING PHOMA LEAF BLIGHT OF FLUTED PUMPKIN USING DIVERSE AGENTS - ndifon, elias mjaika (International Journal of Agricultural Sciences, 2023)
Purpose: Production of fluted pumpkin (Telfaria occidentalis), a very important fruit and leaf vegetable in Africa, is highly constrained by diseases like Phoma blight. Uptodate the pumpkin diseases acknowledged include fungi diseases (two wilts, leaf blight, downy mildew, leaf spot, anthracnose and three fungi storage diseases), three viruses (Telfaria mosaic virus, cucumber mosaic virus and pepper mottle virus), bacteria leaf soft rot and root knot nematodes.Methods: An in vitro research was carried out using completely randomized design with each treatment replicated three times. Two subtrials were conducted to determine the effect of firstly five Trichoderma isolates and secondly of three botanicals on Phoma blight.Findings: Inhibition of Phoma sorghina by Trichoderma isolates ranged between 14-58%. After 144 hours of biocontrol, significant differences (Pâ‰¤0.05) between the treatments in decreasing magnititude of performance followed the order T. virens isolate MZ2, T. harzianum isolate AIBN3, T. harzianum isolate BGMZ3, T. harzianum isolate ZXMZ6 and finally T. harmatum isolate ZXGV5. Also, after 144 hours of exposure, Parkia biglobosa (100%) performed significantly better, followed by P. biglobosa 50% and Juniperus chinensis 100% (which were at par), then Monoon longifolium 100%.Conclusion: Biocontrol and use of botanicals in fluted pumpkin production are feasible options to plant disease managaement in pumpkin production. Further work on integrated management of this disease is ongoing but so much needs to be done when one is dealing with vegetables. Safety and nature of the relationship between the control measures has barely started